A new species of Strobocalyx (Asteraceae: Cichorioideae: Vernonieae) from India - Bhattacharjee, Bandana; Lakshminarasimhan, Pakshirajan; Mukherjee, Sobhan Kumar; Bhattacharjee, Avishek (Phytotaxa, 2017)
Vernonia mastersii, a name first appeared on a herbarium label and then effectively published in ‘Flora of Assam, vol. 3’ by Kanjilal et al., remains invalidly published according to ICN. The description associated with this name is found based on the mixture of two different species, of which one is formally undescribed. Therefore, a new species of Strobocalyx, viz. S. mastersii is described here based on part of the material associated with the invalid name Vernonia mastersii.